Microanalysis of arsenic in solid samples by laser ablation-atomic fluorescence spectrometry. Issue 2 (1st December 2016) - Šlejkovec, Zdenka; van Elteren, Johannes T.; Šelih, Vid S.; Šala, Martin; Corns, Warren T.
Abstract : A spot mode-LA-AFS method has been developed for localised microanalysis of arsenic in biological tissues. Abstract : A spot mode-LA-AFS method has been developed for localised microanalysis of arsenic in biological tissues. The cool argon–hydrogen–air diffusion flame in the detector is able to effectively decompose LA-generated aerosol particles and atomise arsenic for fluorescence detection. After optimisation of the critical LA-AFS parameters through ablation of standards based on cellulose-based filters loaded with various arsenic species, the method was validated by comparison with LA-ICP-MS through measurement of arsenic in the leaflets of the arsenic-hyperaccumulating Chinese ladder brake fern Pteris vittata L. Both methods yielded very similar arsenic concentrations associated with parts of the leaflets. The performance characteristics of the LA-AFS method were as follows: sensitivity, 0.01 mV μg −1 g; detection limit (3× standard deviation of the noise), 11 μg g −1, or, in absolute terms, 30 pg of ablated arsenic; analysis time, ca. 1 min per spot; linearity, 0–40 mg g −1 .